Imagining Imperial Futures: Colonization as the Solution for Urban Uncertainty in Battlestar Galactica. - McKagen, E. Leigh (Canadian Review of American Studies)
In this essay, I argue that the American science fiction television series Battlestar Galactica (2003–2009) reflects uncertainty over survival in the urban present and in the near future, especially how humanity might survive in a closed system with no outside aid or resources. The Colonial Fleet highlights anxieties of contemporary cities driven to the edge of survivability by disaster. Through an examination of the fleet formation throughout the series—and of its survival in the series' conclusion—I argue that Euro-American colonization provides ultimate salvation, soothing the uncertainty present throughout the series narrative, thus presenting an image of a very certain imperial future.